Development of a software application utilising classical efficiency theory, regression and Data Envelopment Analysis in the evaluation of thermal power plant performance. - De Villiers, Almero (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.